2020
DOI: 10.1111/jfbc.13505
|View full text |Cite
|
Sign up to set email alerts
|

Ferulic acid influences Nrf2 activation to restore testicular tissue from cadmium‐induced oxidative challenge, inflammation, and apoptosis in rats

Abstract: Here, we examined the protective effect of ferulic acid (FA) on cadmium chloride (CdCl 2)-mediated reproductive toxicity in male rats. Animals were divided into four groups: control, FA (20 mg/kg), CdCl 2 (6.5 mg/kg), and FA + CdCl 2. CdCl 2 treatment evoked a significant increase in testis cadmium concentration in addition to obvious increase in testosterone, luteinizing hormone, and follicle-stimulating hormone levels. Moreover, CdCl 2-induced oxidative damage through exhausting the cellular defenses (supero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 52 publications
5
22
0
Order By: Relevance
“…Ultra-structurally, cellular vacuolisation, alteration of intercellular spacing, elongated spermatids with loss of chromatin condensation and acrosomal alterations have been identified(de Souza Predes et al, 2011), running in agreement with our findings.In accordance with the results of the current study,Kassab et al (2020) confirmed the ability of Cd to induce oxidant/antioxidant imbalance, where the authors reported an elevation in MDA and NO levels and a reduction in GSH level, associated with suppression of antioxidant enzymatic activities of SOD. Similar to our results, Habib et al (2019) observed a significant Cd-induced decrease F I G U R E 17 Mean SOD level (unit/mg protein) among the study groups (a: significant difference in comparison with control group I; b: significant difference in comparison with caffeine sham control group II; c: significant difference in comparison with antox sham control group III; d: significant difference in comparison with cadmium-treated group IV; e: significant difference in comparison with cadmium + caffeine-treated group V; f: significant difference in comparison with cadmium + antioxidant-treated group VI) F I G U R E 1 6 Mean ROS level (ng/mg protein) among the study groups (a: significant difference in comparison with control group I; b: significant difference in comparison with caffeine sham control group II; c: significant difference in comparison with antox sham control group III; d: significant difference in comparison with cadmium-treated group IV; e: significant difference in comparison with cadmium + caffeine-treated group V; f: significant difference in comparison with cadmium + antioxidant-treated group VI) in testicular 3β-HSD and 17β-HSD gene expression.…”
supporting
confidence: 92%
“…Ultra-structurally, cellular vacuolisation, alteration of intercellular spacing, elongated spermatids with loss of chromatin condensation and acrosomal alterations have been identified(de Souza Predes et al, 2011), running in agreement with our findings.In accordance with the results of the current study,Kassab et al (2020) confirmed the ability of Cd to induce oxidant/antioxidant imbalance, where the authors reported an elevation in MDA and NO levels and a reduction in GSH level, associated with suppression of antioxidant enzymatic activities of SOD. Similar to our results, Habib et al (2019) observed a significant Cd-induced decrease F I G U R E 17 Mean SOD level (unit/mg protein) among the study groups (a: significant difference in comparison with control group I; b: significant difference in comparison with caffeine sham control group II; c: significant difference in comparison with antox sham control group III; d: significant difference in comparison with cadmium-treated group IV; e: significant difference in comparison with cadmium + caffeine-treated group V; f: significant difference in comparison with cadmium + antioxidant-treated group VI) F I G U R E 1 6 Mean ROS level (ng/mg protein) among the study groups (a: significant difference in comparison with control group I; b: significant difference in comparison with caffeine sham control group II; c: significant difference in comparison with antox sham control group III; d: significant difference in comparison with cadmium-treated group IV; e: significant difference in comparison with cadmium + caffeine-treated group V; f: significant difference in comparison with cadmium + antioxidant-treated group VI) in testicular 3β-HSD and 17β-HSD gene expression.…”
supporting
confidence: 92%
“…The analysis of lipid profile levels in this study specified a promising effect of rosinidin for both dosage regimens. These results are in partial agreement with previous results [ 24 ]. Flavonoids are also regarded as safe for use in the treatment of diabetes-related lipid abnormalities as well as other metabolic illnesses, according to clinical evidence [ 25 ].…”
Section: Discussionsupporting
confidence: 93%
“… 71 Nrf2 is a transcriptional mediator with cytoprotective impacts mediated by controlling the expression of an array of antioxidant proteins, such as HO-1. 72 The antioxidant activity of Se has been correlated with the incorporation of Se in selenoproteins and selenoenzyme structures, which can dampen ROS and reduce oxidative damage. 73 In accordance with our findings, the treatment of epileptic mice with Se nanoparticles restored neuronal oxidative damage through the upregulation of GR, SOD, GPx, and CAT mRNA expression, increased GSH levels, and reduced MDA and NO generation, 30 which were attributed to the enhancement of antioxidant regulators (Nrf2/HO-1).…”
Section: Discussionmentioning
confidence: 99%